LANGUAGE ATTITUDES TOWARD REGIONAL ACCENTS AMONG UNIVERSITY STUDENTS - Oliver Smith (International Journal of Literature and Language Studies, 2026)
This article investigates language attitudes toward regional accents among university students within the broader field of linguistics and applied language studies. The study uses questionnaire responses and short written reflections from eighty undergraduate students after listening to accent samples and applies sociolinguistic attitude analysis using rating scales and thematic coding. The main finding is that students associated accents with friendliness, education, urban identity, and professional credibility in uneven ways. The article argues that accent bias remains an important issue for language education, employability, and social inclusion. The discussion is relevant to researchers, teachers, curriculum designers, and graduate students who need concise but systematic models of linguistic inquiry.